Childfree marriage publik figur: Keputusan bersama hidup tanpa anak prespektif syariah dan HAM - Sa’diyah, Halimatus (Maliki Interdisciplinary Journal, 2024)
The phenomenon of childfree marriage has become a controversial issue that is increasingly known and understood by the Indonesian people. Popularized by social media activists or called public figures who give statements that they decide not to have children due to reasons from each of them, especially the assumption that the presence of children provides a great responsibility and this decision becomes a freedom for every couple. The purpose of the study is to provide an explanation of several factors behind childfree marriage carried out by public figures along with views from the side of sharia and human rights on the childfree decision. The research method used is sociological juridical based on youtube analysis with a theological approach, namely the Qur’an and hadith. The results of the study show that many factors are used as reasons for public figures to do childfree, namely from the interests of themselves and their families, accompanied by several sharia views that give consideration to whether or not it is permissible to decide on childfree because the majority of scholars do not support childfree because it is contrary to the purpose of marriage sharia while contemporary scholars argue that childfree is not prohibited by Islamic sharia because there is no evidence that regulates it which can be energized by the opinion of Imam Al Ghazali that the ability of childfree is caused because it endangers life. soul, intellect, heredity, property and religion. Human rights say there is no violation or prohibition when a couple decides to be childfree in their marriage.